Modeling self-perception agents in an opinion dynamics propagation society. (March 2014) - Wang, Sheng-Wen; Huang, Chung-Yuan; Sun, Chuen-Tsai
In previous continuous opinion dynamics models based on bounded confidence assumptions, individuals can only influence each other's opinions when those opinions are sufficiently close; subsequently, agents construct their self-opinions using opinions collected from other agents. All of these models lack the element of an agent's inner self-attitude. In this paper we describe our proposal for a self-perception model in which agents are aware of differences between their attitudes and expressed opinions on specific issues. Our agents are based on a mix of self-perception and cognitive dissonance theory that allows them to self-adjust discomfort caused by inconsistencies between inner attitudes and expressed opinions. Results from a series of simulation experiments indicate that our model captures the gap between inner attitude and external opinion in explaining the private acceptance/public conformity phenomenon. We conclude with a demonstration of how our proposed model can be used in sociological studies of pluralistic ignorance.